A novel red-emitting aggregation-induced emission probe for determination of β-glucosidase activity. (April 2023) - Yao, Bicheng; Zhao, Jiamin; Ding, Siyang; Giel, Marie-Claire; Zhang, Guoqiang; Ding, Dan; Tang, Youhong; Weng, Zhe H.; Hong, Yuning
Abstract: β-Glucosidase (β-Glu) is a ubiquitous enzyme which has multiple roles in medical diagnosis, food production, agriculture, etc. Existing β-Glu assays have limitations such as complex operation, long running time, and high background noise. Here we report a red-emissive probe TBPG for measuring the activity of β-Glu. The probe was synthesized through conjugating a β-Glu targeting glucoside to an aggregation-induced emission (AIE) fluorophore. In the presence of β-Glu, TBPG was hydrolyzed and exhibited a fluorescence turn-on process. The detection conditions including time, temperature, pH value, buffer, and probe concentration were optimized systematically. Afterwards, fluorescence titration was conducted showing an excellent linearity (R 2  = 0.998), a wide linear dynamic range (0–5.0 U/mL), and a limit of detection as low as 0.6 U/L. The detection specificity and ion interference were evaluated by adding various biological species and ions to probe without or with β-Glu. Next, we demonstrate the applicability of probe TBPG in determining the β-Glu activity in living cells using confocal microscopy and flow cytometry. Finally, this newly established assay was applied to real soil samples. Comparable results were obtained as the commercial assay, manifesting its great potential in soil enzyme analysis.